The painful rash - Mokhtar, Norfarina; Jamani, Nurjasmine Aida; Mohamad Kasri, Afiqah (Science Forecast Publications LLC, 2018)
History A26 -year-old woman presents with fever, headache and painful rash on her nose for four days. The rash was burning in nature.She did not have any blurring of vision. She has no other medical illness. On examination, her temperature is 37.50C. Her vital signs are normal.There are multiple vesicular rash with erythematous base over the tip of the nose. There is no other rashes elsewere. The left eyelid is swollen but the conjuntivae is white. Her visual acuity is 6/6. Other examinations are unremarkable. Question 1: What is the most likely diagnosis? Answer: Herpes Zoster opthalmicus. Question 2: What is the most important management for this patient? Answer: Refer Ophthalmology immediately.